Designing power hardware in the loop (PHIL) experiments for various power system applications - Yang, Joshua Hao Wei (Nanyang Technological University, 2020)
Currently, with the rapid advancement in technology, it has become increasingly common for companies to come up with relevant ideas, developing quicker, more reliable and cheaper products in their own specific market circle. Therefore, for companies to be one step ahead of their competition, experiments conducted by the researchers must be done with high accuracy and speed.